A carbon footprint assessment of multi‐output biorefineries with international biomass supply: a case study for the Netherlands. (26th October 2019) - Vera, Ivan; Hoefnagels, Ric; van der Kooij, Aldert; Moretti, Christian; Junginger, Martin
Abstract: The efficient use of lignocellulosic biomass for the production of advanced fuels and bio‐based materials has become increasingly relevant. In the EU, regulatory developments are stimulating the mobilization and production of bio‐based chemicals / materials and biofuels from lignocellulosic biomass. We used an attributional life‐cycle assessment approach based on region‐specific characteristics to determine the greenhouse gas emissions (GHG) performance of different supply‐chain configurations with internationally sourced lignocellulosic biomass (stem wood, forest residues, sawmill residues, and sugarcane bagasse) from the USA, the Baltic States (BS), and Brazil (BR) for the simultaneous production of lactide and ethanol in a biorefinery located in the Netherlands (NL). The results are compared with a biorefinery that uses locally cultivated sugar beets. We also compared GHG emissions savings from the supply‐chain configurations with the minimum GHG saving requirements in the revised Renewable Energy Directive (RED II) and relevant fossil‐based counterparts for bio‐based materials. The GHG emissions 'from cradle to factory gate' vary between 692 g CO2eq /kglactide (sawmill residues pellets from the BS) and 1002 g CO2eq /kglactide (sawmill chips from the USA) for lactide and between 15 g CO2eq /MJethanol (sawmill residues pellets from the BS) and 28 g CO2eq /MJethanol (bagasse pellets from BR) for ethanol. Upstream GHG emissions from the conversion routes have a relatively small impact compared with biomass conversion to lactide and ethanol. The use of woody biomass yields better GHG emissions performance for the conversion system than sugarcane bagasse or sugar beets as result of the higher lignin content that is used to generate electricity and heat internally for the system. Only the sugar beet from the NL production route is able to comply with RED II GHG savings criteria (65% by 2021). The GHG savings from polylactide acid (a derivate of lactic acid) are high and vary depending on choice of fossil‐based counterpart, with the highest savings reported when compared to polystyrene (PS). These high savings are mostly attributed to the negative emission credit from the embedded carbon in the materials. Several improvement options along the conversion routes were explored. Efficient feedstock supply chains (including pelletization and large ocean vessels) also allow for long‐distance transportation of biomass and conversion in large‐scale biorefineries close to demand centers with similar GHG performance to biorefineries with a local biomass supply. © 2019 The Authors. Biofuels, Bioproducts, and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.